Irisin Exerts Inhibitory Effect on Adipogenesis Through Regulation of Wnt Signaling - Ma, Eun Bi; Sahar, Namood E.; Jeong, Moonsup; Huh, Joo Young (Frontiers in Physiology, 2019)
Irisin is an exercise-induced myokine known to induce adipocyte browning through induction of uncoupling protein 1. Recent studies have reported that irisin is also an adipokine. However, there is limiting evidence on the role of endogenous irisin from adipocytes. In this study we aim to elucidate the expression and secretion pattern of irisin during adipocyte differentiation and the role of endogenous and exogenous irisin on the adipogenic process. As such, recombinant irisin, plasmid expressing FNDC5 and small interfering RNA were utilized. Our results show that the gene expression of irisin precursor FNDC5 and irisin secretion increases at the early stage of adipogenesis. Both recombinant irisin treated cells and FNDC5-overexpressed cells resulted in inhibition of adipogenesis evidenced by downregulated C/EBP, PPAR, and FABP4 expression and reduced lipid accumulation. Further data showed that the inhibitory effect of irisin on adipogenesis is mediated though potentiation of Wnt expression, which is known to determine the fate of mesenchymal stem cells and regulate adipogenesis. Conversely, FNDC5 knockdown cells showed downregulated Wnt expression, but failed to further induce adipogenesis. This study suggests that both exogenous and endogenous irisin is able to inhibit adipogenesis and that activation of Wnt and subsequent repression of transcription factors is partly involved in this process. This provides a novel insight on the local effect of irisin on adipocytes and additional benefit to protect against obesity-related metabolic disorders.